Multimodalidade em artigos científicos : impactos na leitura de estudantes universitários - Menezes, Talita Santos (2023)
This study presents a discussion about the reading of the textual genre scientific article, from a multimodal perspective in linguistic studies. We developed this study from the following problem: in a scientific article, does the presence of multimodal resources, especially illustrative ones, impacts college students' reading? Assuming multimodality as the integration between verbal and visual modes of representation in textual materiality (MAYER, 2005), we suppose that graphic, spatial, and, especially, illustrative elements - present in the composition of the scientific article - might assist in reading comprehension. The emphasis put on illustrative elements is justified by the use of resources associated with reading comprehension that are not limited to the textual surface, but deal with specific ways of summarizing information in visual formats. This research field is fundamentally based on the principles dictated by the Cognitive Theory of Multimedia Learning (CTML). Moreover, this study also brings together theoretical assumptions about reading, scientific articles, multimodality, and illustrative elements. We conducted this research in a post-pandemic context, with the voluntary participation of 116 undergraduate students from the first academic semester (2022.1) of Foreign and Vernacular Language, from the Federal University of Sergipe (UFS). We adopted a comparative method of data collection, with participants randomly divided into two groups: Group A (n=58) and Group B (n=58). Group A read a scientific article in which there were three types of illustrations (figures, tables, and graphs), and Group B read the same article, but without the presence of the mentioned illustrations. After reading the material, both groups answered a questionnaire that evaluated: a) the undergraduate students’ experience with multimodality and reading of academic texts; b) the students' reading comprehension of the article content; and c) the participants' social and educational profile. The corpus of analysis that we conducted consisted of the answers to these 116 questionnaires, which were subjected to statistical manipulation, and descriptive and inferential analysis. We identified three main results. First, the three categories of multimodal elements usually adopted in the composition of scientific articles are graphic elements (font, color, style, size, and graphic signs), spatial elements (indentation, line spacing, and position on the page), and illustrative elements (figure, table, graph, and chart). Second, from the category of illustrations, figures are the most used element, and their distribution in the scientific article varies from one section to another. In addition to that, we also observed that the results and discussions sections contain a major number of illustrations. Charts, graphs, and tables were only used after the methodology section, which may reinforce the function of these illustrations in summarizing data for a better reading understanding. Third and finally, regarding the understanding of articles with/without illustrations, there were no statistically significant differences between group A and group B. Group B, in comparison with group A, achieved a higher mean score in the questionnaire answered after reading the scientific article, which suggests that the presence of illustrations in the text read by group A was not a determining factor for the participants' comprehension, contrary to what CTML dictates. Based on that, we argued that reading demands brought by the participants from basic education, as well as the impact of the pandemic on the learning of Brazilian students, are factors that may be directly associated with the results we obtained in this study, which suggests that the effectiveness of the multimedia principle of TCAM, in the context of the academic community of UFS, may be subject to the level of training of students, being applied only to college students who already have specific skills for reading multimodal materials.